Workplace Stress and Burnout: A Qualitative Exploration of Respiratory Therapist Experiences in the Level II Private Hospitals in Cavite - Triñanes, Ronald Jezter; Faller, Erwin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of respiratory therapists regarding workplace stress and burnout in selected Level II private hospitals in Cavite. Anchored on the Job Demands–Control Theory and Maslach’s Burnout Theory, the study examined how respiratory therapists perceived workplace stress and burnout, the workplace factors contributing to these experiences, the coping mechanisms they used, and the effects of burnout on professional performance, personal well-being, and relationships with colleagues and patients. A qualitative phenomenological research design was employed. Eighteen licensed respiratory therapists were selected through stratified purposive sampling from a population of 35 respiratory therapists across six hospital groups. Data were gathered using a researcher-developed semi-structured interview guide validated by three senior respiratory therapists and were analyzed through thematic analysis. Findings revealed that workplace stress and burnout were mainly caused by understaffing, excessive workload, inadequate resources, long working hours, low compensation, limited career growth, poor leadership support, interpersonal conflicts, and role devaluation. These conditions resulted in physical exhaustion, emotional strain, cognitive fatigue, reduced motivation, compromised care quality, strained workplace relationships, and challenges in patient interaction. Despite these difficulties, participants used coping strategies such as rest, family and peer support, teamwork, cognitive reframing, spirituality, mindfulness, hobbies, and professional commitment. The study concludes that while individual coping strategies help respiratory therapists manage stress temporarily, institutional, and policy-level interventions are needed to address the structural causes of burnout. The study supports SDG 3 on Good Health and Well-Being, SDG 8 on Decent Work and Economic Growth, and, to a limited extent, SDG 16 on Strong Institutions. Its sustainability impact lies in promoting healthcare workforce well-being, improving institutional support systems, and sustaining quality respiratory care services.
Keywords: Burnout; Coping Mechanisms; Respiratory Therapists; Workplace Stress; Philippines